Perbandingan Mutu Fisikokimia Virgin Coconut Oil (VCO) dengan Metode Enzimatis dan Fermentasi Alami Mutu Fisikokimia Virgin Coconut Oil (VCO) dengan Metode Enzimatis dan Fermentasi Alami - Dewi Maharani Indah Sari, Ni Komang; Chandra Wibawa, Agung Ari; Pramitha, Dewa Ayu Ika; Megawati, Fitria (Usadha, 2024)
VCO is obtained from fresh, old coconut (Cocos nucifera L) flesh through a simple process without heating. Making VCO can be done by several methods, namely enzymatic methods and natural fermentation. The enzyme used in the manufacture of VCO is bromelain enzyme powder. The purpose of this study was to determine differences in the physicochemical quality of Virgin Coconut Oil (VCO) obtained by natural fermentation methods and VCO obtained by enzymatic methods adding 10% bromelain enzyme. The type of research used is experimental research conducted in the laboratory. The results obtained were then evaluated to determine the physicochemical quality of enzymatic VCO and natural fermentation. Physicochemical test parameters include a water content test performed by the gravimetric method and a free fatty acid test carried out by the titrimetric method. Based on the research that has been done, the highest average yield of VCO with the addition of bromelain enzyme powder is (24.45 ± 0.06) %. The results of the pH test on sample 1 (S1) and sample 2 (S2) obtained a pH value of 6. Testing the water content of the two samples S1 and S2 obtained results (4.018 ± 1.93) and (7.949 ± 2.57) %, with statistical testing getting p> 0.05 where there is no significant difference between the two samples. Tests for free fatty acid levels in samples S1 and S2 yielded (0.0086 ± 0.003055) % and (0.0106 ± 0.004619) %, with statistical testing yielding p > 0.05 after being tested by Kruskal Wallis, no there is a significant difference between the two samples. The enzymatic production of VCO has the advantage of obtaining more yield with the same quality as naturally fermented VCO.